2012
DOI: 10.1038/ja.2012.76
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive anthraquinone dimers from the leafhopper pathogenic fungus Torrubiella sp. BCC 28517

Abstract: Torrubiellins A (1) and B (2), two new dimeric anthraquinones were isolated from the leafhopper pathogenic fungus Torrubiella sp. BCC 28517. The structures of the new compounds were elucidated by analyses of the NMR spectroscopic and mass spectrometry data. Torrubiellin B (2) exhibited broad range of biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…Comparison of the MS and NMR data of 1 with those previously reported for torrubiellin B suggested that they are identical. 17 The structure of 1 was finally confirmed as torrubiellin B by careful analysis of COSY, HMBC, and ROESY correlations. Interpretation of the COSY and HMBC correlations shown in Figure 2 revealed two anthracene moieties being fused via a cyclopentene ring.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Comparison of the MS and NMR data of 1 with those previously reported for torrubiellin B suggested that they are identical. 17 The structure of 1 was finally confirmed as torrubiellin B by careful analysis of COSY, HMBC, and ROESY correlations. Interpretation of the COSY and HMBC correlations shown in Figure 2 revealed two anthracene moieties being fused via a cyclopentene ring.…”
Section: Resultsmentioning
confidence: 88%
“…H-10 0 showed ROE correlations to H-5 0 and H-11 eq and furthermore H-11 eq had a correlation to H-2, thus indicating the (5 0 S ⁄ ,10 0 R ⁄ ,10a 0 S ⁄ ) relative configuration of 1 as shown in Figure 4, which is in agreement with that previously reported. 17 Torrubiellin B may be viewed as a 4,5 0 -linked heterodimeric biaryl of 7-hydroxyemodin and 1,8,10-trihydroxy-6-methyl4a,10-dihydroanthracen-9(4H)-one, in which the rotation along the biaryl axis is blocked by the methylene linker between C-3 and C-10a. In contrast to axially chiral biaryls of anthracene-9,10-dione monomers, 18 torrubiellin B has only central chirality elements due to the C-5 0 , C-10, 0 and C-10a 0 chirality centers and the projection angle between the planes of the two monomers is governed by the central chirality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 162 are antimalarial, antifungal and antibacterial [53]. Another insect pathogen Aschersonia paraphysata BCC 11964 produces aschernaphthopyrones A (164, Scheme 10) and B (165, Scheme 10), two new biarylic dihydronaphthopyrones [54].…”
Section: Quinonesmentioning
confidence: 99%